1976
DOI: 10.1002/jcp.1040890431
|View full text |Cite
|
Sign up to set email alerts
|

Transport changes associated with growth control and malignant transformation

Abstract: We can distinguish two classes of membrane transport changes in cultured cells: (a) growth-rate contingent changes are those which occur in coordination with the onset of density-dependent inhibition of growth; (b) transformation-specific changes are those which occur when cells become transformed, and which can be detected even when normal and transformed cells are growing at the same rate. Growth-rate contingent changes include the density-dependent changes in phosphate, nucleoside, glucose, amino acid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…It is of interest that the experiment shovyn in Table 3 may indicate that SV-transformed 3T3 cells take up putrescine less rapidly than normal 3T3 cells. This result is the opposite of the well known enhanced transport of certain amino acids and sugars in virally transformed cells (Foster & Pardee, 1969;Isselbacher, 1972;Weber et al, 1976;Dubrow et al, 1978). However, it should be stressed that the uptake of radioactivity measured in the present experinments merely indicates the maximal rate of net uptakce of the added putrescine and may not reflect a true rate of transport because of complications that may arise from further metabolism, a difference in the starting intracellular putrescine concentratipn, and the possibility that some of the putrescine is merely tightly adsorbed to the cell surface.…”
Section: Vol 180mentioning
confidence: 73%
See 1 more Smart Citation
“…It is of interest that the experiment shovyn in Table 3 may indicate that SV-transformed 3T3 cells take up putrescine less rapidly than normal 3T3 cells. This result is the opposite of the well known enhanced transport of certain amino acids and sugars in virally transformed cells (Foster & Pardee, 1969;Isselbacher, 1972;Weber et al, 1976;Dubrow et al, 1978). However, it should be stressed that the uptake of radioactivity measured in the present experinments merely indicates the maximal rate of net uptakce of the added putrescine and may not reflect a true rate of transport because of complications that may arise from further metabolism, a difference in the starting intracellular putrescine concentratipn, and the possibility that some of the putrescine is merely tightly adsorbed to the cell surface.…”
Section: Vol 180mentioning
confidence: 73%
“…However, the very low extracellular concentrations at which these exert effects on ornithine decarboxylase (which are substantially less than the normal intracellular concentrations, unless most of the intracellular polyamine is bound to macromolecular anions) renders this an attractive hypothesis. It is known that viral transformation of mouse fibroblasts results in the alteration of membrane characteristics including changes in the content of glycolipids, glycoproteins and surface proteins as well as changes in the transport of sugars and amino acids (Van Nest & Grimes, 1977;Weber et al, 1976;Isselbacher, 1972;Dubrow et al, 1978). It is possible that a change in the receptor site for putrescine or spermidine might be responsible for the lack of sensitivity of the SV-transformed cells.…”
Section: Vol 180mentioning
confidence: 99%
“…Furthermore, there is evidence of an association of potassium and amino acid transport in cultured non-brain tumor cells. The cellular uptake of K ~ and the nonmetabolized amino acid 0t-aminoisobutyric acid (~-AIB) increases around the S-G 2 interface of the cell cycle [20] and decreases when cells are inhibited for growth [21]. It has also been suggested that a single protein kinase, induced by growth factor receptor activation, regulates independently a NaCI/KCI symporter and amino acid transport systems [1].…”
Section: Discussionmentioning
confidence: 99%
“…37 The fluidity of the phospholipid components in these cells is altered in such a way as to create more rigidity in the cell membranes. It is believed that the cytochrome P1-450 and the reductase portions of the AHH complex are enclosed in a phospholipid matrix within the membrane of the endoplasmic reticulum.…”
Section: Cancer June 1978mentioning
confidence: 99%